Modeling and Simulation Affect of Binder Addition Rate on Ammonia Emission During Granulation Process - Mohamad, N.; Shafeeq, D.; Shaaban, A.; Nurhuda, M.A. (Journal of Advanced Manufacturing Technology (JAMT), 2017)
This paper presents the modeling and simulation of binder addition in Fluidized bed granulator in order to quantify the amount of ammonia (NH3) gas release. The model development is based on experimental observations using MATLAB 12b with the ability of combining expert knowledge with mapping of experimental data sets is expected to establish a robust model which then taken up for process optimization and control the ammonia emission.